MEMS-based LC tank with extended tuning range for low phase-noise VCO. Issue 2 (29th October 2015) - Cazzorla, Alessandro; Farinelli, Paola; Urbani, Laura; Cacciamani, Fabrizio; Pelliccia, Luca; Sorrentino, Roberto; Giacomozzi, Flavio; Margesin, Benno
Abstract : This paper presents the modeling, manufacturing, and testing of a micro-electromechanical system (MEMS)-based LC tank resonator suitable for low phase-noise voltage-controlled oscillators (VCOs). The device is based on a variable MEMS varactor in series with an inductive coplanar waveguide line. Two additional parallel stubs controlled by two ohmic MEMS switches have been introduced in order to increase the resonator tunability. The device was fabricated using the FBK-irst MEMS process on high resistivity (HR) silicon substrate. Samples were manufactured with and without a 0-level quartz cap. The radio frequency characterization of the devices without 0-level cap has shown a continuous tuning range of 11.7% and a quality factor in the range of 33–38. The repeatability was also tested on four samples and the continuous tuning is 11.7 ± 2%. Experimental results on the device with a 0-level cap, show a frequency downshift of about 200 MHz and a degradation of the quality factor of about 20%. This is, most likely, due to the polymeric sealing ring as well as to a contamination of the ohmic contacts introduced by the capping procedure. A preliminary design of a MEMS-based VCO was performed using Advanced Design System and a hardwired prototype was fabricated on Surface Mount Technology on RO4350 laminate. The prototype was tested resulting in a resonance frequency of 5 GHz with a phase noise of −105 and −126 dBc at 100 KHz and 1 MHz, respectively, and a measured output power of −1 dBm.